Estudio de factibilidad para el desarrollo de un sistema web en el control de ventas y compras de productos del Comercial ‘Don Wuacho de la ciudad de Babahoyo - España Santillán, Karla Elizabeth (2021)
The advancement of web systems evolved every day more in different fields, both educational and commercial in a gigantic way, in such a way that the way of carrying out the information management processes within each organization is transcended, in order to find these Huge changes is a requirement to create new technologies and adapt them to the demands that each organization requires. This case study is developed under the line of research Information and communication systems, entrepreneurship and innovation and subline Networks and intelligent software and hardware technologies; whose fundamental objective is to establish the feasibility for the development of a web system in the commercial "Don Wuacho" of the city of Babahoyo, through the analysis of theoretical and methodological bases; In addition to the respective technical feasibility study where it was determined through the comparison of different programming languages and data system managers which was the most feasible for said system, in the economic feasibility the respective costs were stipulated where it could be verified that the project is economically viable, in addition to optimizing time, and above all, the secure registration of information and finally in the operational feasibility the human resources necessary for the development of the system were established, in order to improve the control of sales and purchases of products in said establishment, the research was descriptive and the methodology used is the interview and the observation that were of great help to know the problems of the commercial.